Psychoanalytical Interpretation of the Intersex Relations in S. Protsyuk’s Novel «Infection» - Melniichuk , Vladyslav (Philological Treatises, 2020)
The article is devoted to the analysis of the artistic world of the S. Protsyuk’s novel “Infection” The selected a priori schemes-matrices in the research help to find the complexes around which the author’s imagination begins to work and to create the artistic world of the future work. The partially explained process of formation of the writer’s novels helped to outline certain unconscious components and supplanted desires of the artist. The analysis of the character’s dreams, his fantasies and visions reveals to the recipient the undisguised archetype of the writer’s Anima. The considering hero’s unconscious states around this matrix explain us several complexes. The identified features make it possible to assert their presence in creator’s person. Our creative search involves the explanation of the intersex relations of the characters with the help of the archetype of Anima, which forces the person to unconscious actions. It includes: attraction to persons of the opposite sex, neurotic perception of reality, donjuanism, the emergence of fantasies and dreams, which opens a broader picture of the psyche of the individual. This archetype often finds its expression in the work and is clearly manifested in the love lines of the novel, so it would be wrong to ignore it. The comparison of the features of the protagonist’s wife and his mother shows us the similarity and correspondence of the heroines. Analysis of the dreams and fantasies of the hero indicates that the hero lived at the expense of women. This statement is confirmed by the interpretation of the following dreams and fantasies in the article. The consideration of the childhood reveals to us the main reason for the betrayal of the hero, because there we find two complexes: the Oedipus complex and the Mother complex. The detected complexes become the cause of neurotic perception of reality and unstable psyche.